A case of penetrating neck injury in zone II treated with combined endovascular and surgical management - Youhei Nakamura; Shunichiro Nakao; Takeshi Nishida; Hiroshi Ito; Tomohiko Ozaki; Jun Oda (Acute Medicine & Surgery)
Abstract Background We report a case of zone II penetrating neck trauma with active bleeding in which endovascular treatment was performed prior to neck exploration to identify and control the bleeding point. Case Presentation A man in his 50s presented to our emergency department in hemorrhagic shock stemming from a penetrating knife wound injury to the right side of his neck. He was bleeding massively from the right neck wound and oral cavity. Cervical angiography showed bleeding from the right external carotid artery and intimal injury to the right internal carotid artery. Balloon occlusion at the common carotid artery origin and distal to the injured internal carotid artery controlled active bleeding. During vascular balloon occlusion, definitive hemostatic treatment was achieved through ligation of the proximal external carotid artery. Conclusion Neck exploration combined with endovascular treatment may be one option as a treatment strategy for patients with zone II penetrating neck injury.